2016
DOI: 10.1186/s40064-016-3543-0
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of mutations, gene expression changes and fusion transcripts by whole transcriptome RNAseq in docetaxel resistant prostate cancer cells

Abstract: Docetaxel has been the standard first-line therapy in metastatic castration resistant prostate cancer. The survival benefit is, however, limited by either primary or acquired resistance. In this study, Du145 prostate cancer cells were converted to docetaxel-resistant cells Du145-R and Du145-RB by in vitro culturing. Next generation RNAseq was employed to analyze these cell lines. Forty-two genes were identified to have acquired mutations after the resistance development, of which thirty-four were found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…It is also likely to be that CDPCs have altered expression of drug transporter proteins, thus making them less susceptible to docetaxel toxicity. ( Aberuyi et al , 2014 ; Rahgozar et al , 2014 ; de Morree et al , 2016 ; Ma et al , 2016 )…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely to be that CDPCs have altered expression of drug transporter proteins, thus making them less susceptible to docetaxel toxicity. ( Aberuyi et al , 2014 ; Rahgozar et al , 2014 ; de Morree et al , 2016 ; Ma et al , 2016 )…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the potential role of GLYATL1 in prostate cancer, we analyzed its expression in prostate cancer cell lines. In their study on next‐generation RNAseq in castration‐resistant prostate cancer cell lines, Ma et al found GLYATL1 among the top 8 downregulated genes in PC3 and DU145 (which represent acquired resistance to androgens) vs LNCaP cells. In line with that, we found GLYATL1 to be present in prostate cancer cell lines that express AR (LNCaP, C4‐2B, VCaP, and 22Rv1) and absent in DU145, PC3, benign prostate epithelial cells and RWPE‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Although mutational analysis of transcripts is restricted following removal of InDel mutations and A:T>G:C conversions largely produced by RNA editing [16], all other mutations in coding regions can be successfully analyzed, as was the case in liver and prostate cancer [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq is a high-throughput procedure that provides extensive data on genomic alterations with numerous advantages over hybridization-based transcriptome analysis, like detection of rare and alternative transcripts, splice variants, mutations, and quantification of transcript expression [22] . Although mutational analysis of transcripts is restricted following removal of InDel mutations and A:T>G:C conversions largely produced by RNA editing [16] , all other mutations in coding regions can be successfully analyzed, as was the case in liver and prostate cancer [23] , [24] .…”
Section: Discussionmentioning
confidence: 99%